2015
DOI: 10.1155/2015/712093
|View full text |Cite
|
Sign up to set email alerts
|

Life History of an Endangered Marine InsectHalovelia septentrionalisEsaki (Hemiptera: Veliidae)

Abstract: Halovelia septentrionalis Esaki is one of the endangered marine water striders found along the Japanese coast. It is of primary importance to investigate its life history in the field so as to develop conservation measures as well as to understand how this species has adapted to marine environments. We studied its life history in Misaki on the southern part of the Miura Peninsular near Tokyo, ca. 35 ∘ N, probably the northernmost locality not only for H. septentrionalis but also for any Halovelia species, mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In 2016, as a part of the Super Science High School (supported by the Japan Science and Technology Agency) programmes improving biology education and research, we initiated a project to survey detailed distributional patterns and ecology of coastal marine water striders; namely Asclepios shiranui (Esaki), Halobates japonicus Esaki, and Halobates matsumurai Esaki (Gerridae: Halobatinae); and the riffle bug Halovelia septentrionalis Esaki (Hemiptera: Veliidae: Haloveliinae). These are all designated as endangered or vulnerable by the national and/or local governments (Ikawa and Nakazawa 2015), but our observations suggested that these species were exceptionally abundant within Omura Bay and its adjacent coastline. The fauna of the marine water strider and riffle bug in the bay was previously reported by Hayashi and Miyamoto (2003), who confirmed Asclepios shiranui and Halovelia septentrionalis at only one locality (site 4).…”
Section: Introductionmentioning
confidence: 59%
“…In 2016, as a part of the Super Science High School (supported by the Japan Science and Technology Agency) programmes improving biology education and research, we initiated a project to survey detailed distributional patterns and ecology of coastal marine water striders; namely Asclepios shiranui (Esaki), Halobates japonicus Esaki, and Halobates matsumurai Esaki (Gerridae: Halobatinae); and the riffle bug Halovelia septentrionalis Esaki (Hemiptera: Veliidae: Haloveliinae). These are all designated as endangered or vulnerable by the national and/or local governments (Ikawa and Nakazawa 2015), but our observations suggested that these species were exceptionally abundant within Omura Bay and its adjacent coastline. The fauna of the marine water strider and riffle bug in the bay was previously reported by Hayashi and Miyamoto (2003), who confirmed Asclepios shiranui and Halovelia septentrionalis at only one locality (site 4).…”
Section: Introductionmentioning
confidence: 59%